PENGARUH PENGALAMAN KERJA DAN PENILAIAN PRESTASI KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA PT. JASARAHARJA PUTERA CABANG PEKANBARU - Said Muamarizal; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research conducted in PT. Jasaraharja Putera branch Pekanbaru in order to analyze the effect of job experience and performance assessment on employee’s career development. Both primary or secondary data used in this study, in which those datas are collected by using questioner. Population consist of entire employees. Sample technique by cencus is used consist of 41 employees. Job experience and performance assessment used as independent, while career development is dependent variable. Data analyzed by using descriptive and multiple linier regression analysis assisted by SPSS 17 for windows. This study reveals that job experience and performance assessment influence significantly, either simultaneously or partially, on employee’s career development. Performance assessment gives stronger effect to career development than the effect given by job experience. This research urges some recommendation to management in order to enhance the experience quality by delivering training, job rotation and adjust competence and intention along with the job position. Performance assessment need to be enhanced by conducting workload analysis, implementing a consistence sanction and sending employees into motivational seminars.Keywords: Job Experience, Performance Asessment and Career Development